Conserving Biodiversity - Institutions, Policies and Incentives - Carl Binning (New Zealand Government, The Treasury, 2000)
Biological diversity, a term that encapsulates all of life - the diversity of plants and animals and the places they live, has changed the way we think about nature conservation. The conservation of biodiversity demands that we understand the role of natural systems and ecological processes in sustaining landscapes. Landscapes and the issues embedded within them vary enormously from the protection of remote wilderness areas to maintaining the productivity of agricultural regions and the quality of life within cities. This report seeks to answer questions from an outsider's perspective about the roles central government, regional councils and the non-government sector should play in conserving biodiversity; how effective working partnerships with landholders should be developed; what the most appropriate policy mix is; and who should fund biodiversity conservation programmes. It draws on Australian and international experience in the management of biodiversity. In consultations with officials and stakeholders mixed views were expressed on whether holistic approaches to biodiversity conservation are required or whether a model of protection through dedicated public and private (covenanted) conservation reserves will be sufficient. The view taken in this report is that protection is necessary but not sufficient. Ultimately on- ground programmes are required that target and reward land managers who actively manage areas of indigenous biodiversity on their land. However, it is also necessary to understand the economic and social factors that are driving the land-uses and management practices that are causing the continuing loss of biodiversity. Successful approaches to biodiversity conservation require coordinated responses from all scales of management. The critical role of regional planning in balancing the need for scientific assessment, leadership and centralised planning from the "top down" with strategies for engaging landholders and local communities from the "bottom up" is highlighted. The Resource Management Act 1991 (RMA) provides a solid framework for developing effective regional responses. However the challenges of coordination across spheres of government, clarification of regulation and engaging the non-government sector remain. A number of policy options, such as funding and tax incentives and capacity building, are suggested to address these.
Keywords: 330